2020
DOI: 10.3390/ma13081895
|View full text |Cite
|
Sign up to set email alerts
|

Study on Springback Straightening after Bending of the U-Section of TC4 Material under High-Temperature Conditions

Abstract: The thin-walled structures of titanium alloys have peculiar characteristics involving thin curved surfaces, complicated structures, and a poor rigidity. Therefore, bending or twisting distortion frequently occurs in forging, extrusion, drawing, transportation, cooling, and manufacturing. Straightening theory focuses on the straightening curvature or bending moment at room temperature, and a unified analytical model of the straightening curvature, the straightening bending moment, and the straightening stroke, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…where ρa and ρb are the radius after and before springback, D and E are the hardening modulus and the elastic modulus, σs and t are the yield strength and the thickness of sheet, respectively. To predict the springback of anisotropic materials, including titanium alloys, the effect of anisotropy (asymmetry in the yielding and hardening stage) on springback cannot be neglected [100,101]. Zhang et al found that springback would be overestimated by applying the isotropic hardening model [102].…”
Section: Prediction Methods Of Springback Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ρa and ρb are the radius after and before springback, D and E are the hardening modulus and the elastic modulus, σs and t are the yield strength and the thickness of sheet, respectively. To predict the springback of anisotropic materials, including titanium alloys, the effect of anisotropy (asymmetry in the yielding and hardening stage) on springback cannot be neglected [100,101]. Zhang et al found that springback would be overestimated by applying the isotropic hardening model [102].…”
Section: Prediction Methods Of Springback Behaviorsmentioning
confidence: 99%
“…In comparison to the springback results, it was found that asymmetry would cause an increase in springback of hexagonal close-packed sheet metals compared with using a symmetric material model, as shown in Figure 13. To predict the springback of anisotropic materials, including titanium alloys, the effect of anisotropy (asymmetry in the yielding and hardening stage) on springback cannot be neglected [100,101]. Zhang et al found that springback would be overestimated by applying the isotropic hardening model [102].…”
Section: Prediction Methods Of Springback Behaviorsmentioning
confidence: 99%
“…Different parameter settings return differently straightened billets [5]. The crucial thing is to achieve accurate prediction of spring back [20,21] after releasing the straightening force. To achieve fast calculations, analytical and semianalytical approaches are currently used.…”
Section: Three-point Bendingmentioning
confidence: 99%
“…The structural components in spacecraft require further improvement of the low-temperature performance required by the equipment environment. The alloy must meet the requirements of sufficient strength and toughness at low temperatures, excellent thermal properties and good machinability because of the complex shape of the structural parts [6]. At low temperature, titanium alloy has higher yield strength than traditional alloy, which is more than three times of stainless steel, and the density is only half of stainless steel [7].…”
Section: Introductionmentioning
confidence: 99%